2016
DOI: 10.1177/1403494816668082
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between literacy skills and self-reported health in the Nordic countries

Abstract: Aims: This study investigated the association between literacy skills and self-reported health among Danish (n = 7284), Finnish (n = 5454), Norwegian (n = 4942) and Swedish (n = 4555) participants aged 16–65 years. Methods: Logistic regression models were used to assess the association between literacy skills and self-reported health after adjusting for sex, age and educational level. Results: Nordic participants aged 16–65 years with literacy skills at the lowest level reported sub-optimal health more often (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(48 reference statements)
2
7
0
3
Order By: Relevance
“…Many studies confirm the association between self-reported health status and educational attainment [9,10,47] but, to the best of our knowledge, no study report on students at different educational levels and educational program in VET education. In accordance with our findings (Table 3), other studies have found positive associations between health literacy and self-reported health status in general populations, including younger adults [47,49,50], although the directionality of this association is still unsupported.…”
Section: Interpretationssupporting
confidence: 92%
“…Many studies confirm the association between self-reported health status and educational attainment [9,10,47] but, to the best of our knowledge, no study report on students at different educational levels and educational program in VET education. In accordance with our findings (Table 3), other studies have found positive associations between health literacy and self-reported health status in general populations, including younger adults [47,49,50], although the directionality of this association is still unsupported.…”
Section: Interpretationssupporting
confidence: 92%
“…Health literacy might represent a determinant of health behaviours (Liu, Liu, Li, & Chen, 2015; Osborn, Paasche‐Orlow, Bailey, & Wolf, 2011). Previous research has reported relationships between health literacy and lifestyle profiles (Aaby, Friis, Christensen, Rowlands, & Maindal, 2017; Adams et al., 2013; Friis, Lasgaard, Rowlands, Osborne, & Maindal, 2016; Friis, Vind, Simmons, & Maindal, 2016; Husson, Mols, Fransen, Van De Poll‐Franse, & Ezendam, 2015; Lundetræ & Gabrielsen, 2016; MacAbasco‐O'Connell et al., 2011; Osborn et al., 2011; Park et al., 2017). Low levels of health literacy have been associated with more adverse health behaviours such as smoking, physical inactivity and poor diet and poor subjective health but inconclusive results have been reported.…”
Section: Introductionmentioning
confidence: 99%
“… 12 At any rate, low health literacy has been related to more adverse health behaviours 13 15 and poor subjective health. 5 , 13 18 However, all these studies were either small and/or investigated health literacy as basic skills of reading and understanding. No more comprehensive studies have explored these associations.…”
Section: Introductionmentioning
confidence: 99%